Energy Storage Devices 2019
DOI: 10.5772/intechopen.85166
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Redox Flow Batteries: Electrochemical Engineering

Abstract: The importance of reliable energy storage system in large scale is increasing to replace fossil fuel power and nuclear power with renewable energy completely because of the fluctuation nature of renewable energy generation. The vanadium redox flow battery (VRFB) is one promising candidate in large-scale stationary energy storage system, which stores electric energy by changing the oxidation numbers of anolyte and catholyte through redox reaction. This chapter covers the basic principles of vanadium redox flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The discharge capacity decreases with the increase of the current density as shown in Figure 1. This result proves that energy density decreases when current density increases and power density increases as mentioned by Sangwon Kim [21]. This appears to be the case where decrease in energy density will increase the power density, thus it will lower the energy discharge from the battery.…”
Section: Discharge Capacitysupporting
confidence: 69%
“…The discharge capacity decreases with the increase of the current density as shown in Figure 1. This result proves that energy density decreases when current density increases and power density increases as mentioned by Sangwon Kim [21]. This appears to be the case where decrease in energy density will increase the power density, thus it will lower the energy discharge from the battery.…”
Section: Discharge Capacitysupporting
confidence: 69%
“…The energy density of the complete system that makes up the VRFB is smaller than the ones calculated by (13). Theoretically, the energy density of VRFB systems is about 28 Wh/L, but in real applications it has been found that the ranges go from 15 to 25 Wh/L [84].…”
Section: Tank Sizingmentioning
confidence: 81%
“…As it can be seen in Table 4, two tanks of 400 L capacity would be needed. This would represent a total amount of approximately 732 kg of H 2 SO 4 which is the solvent, and 178 kg of vanadium species which represent the solutes that react inside the cell, based on the molar mass of the electrolyte species [84,87]. These amounts of chemical species have been calculated taking into account the typical value of vanadium ion concentration, which, as explained, usually is 2 M.…”
Section: Examplementioning
confidence: 99%
“…In particular, if new membranes with improved selectivity in highly concentrated solutions will be available, the ABFB capacity could be increased remarkably. Notably, even with a 2 M acid–base concentration (for a NaCl-HCl-NaOH system), the ABFB power density would be comparable with vanadium redox flow batteries [ 47 ]. Overall, the chemistry of the ABFB electrolyte is still largely unexplored, as all the reported studies so far focus only on the NaCl-HCl-NaOH system, with NaCl concentration in the range of 0.1 to 1 M (see Table 1 ).…”
Section: Battery Components and Designmentioning
confidence: 99%